The pathway to open disclosure. Issue 4 (July 2015) - Segobiano, Aaron; Lockhart, Lisa; Davis, Charlotte
<x xml:space="preserve">Abstract</x> By acknowledging medical errors through transparency and provider engagement, we can improve healthcare quality and outcomes.